2004
DOI: 10.1007/s00702-004-0220-1
|View full text |Cite
|
Sign up to set email alerts
|

High dose vitamin E therapy in amyotrophic lateral sclerosis as add-on therapy to riluzole: results of a placebo-controlled double-blind study

Abstract: Neither the primary nor the secondary outcome measures could determine whether a megadose of vitamin E is efficacious in slowing disease progression in ALS as an add-on therapy to riluzol. Larger or longer studies might be needed. However, administration of this megadose does not seem to have any significant side effects in this patient population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
94
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 169 publications
(96 citation statements)
references
References 27 publications
1
94
0
1
Order By: Relevance
“…Two double-blind, placebo-controlled, randomized trials have been performed, administering to sporadic ALS patients 500 and 5000 mg of Vitamin E per day, respectively. Both trials demonstrated no significant differences with respect to placebo, although a trend toward improvement was shown in those patients receiving Vitamin E [21]. A lack of significant associations between intakes of antioxidant Vitamins and ALS risk was also reported in two case-control studies, but both were too small to estimate the specific effect of Vitamin E supplementation [22].…”
Section: Amyotrophic Lateral Sclerosismentioning
confidence: 96%
“…Two double-blind, placebo-controlled, randomized trials have been performed, administering to sporadic ALS patients 500 and 5000 mg of Vitamin E per day, respectively. Both trials demonstrated no significant differences with respect to placebo, although a trend toward improvement was shown in those patients receiving Vitamin E [21]. A lack of significant associations between intakes of antioxidant Vitamins and ALS risk was also reported in two case-control studies, but both were too small to estimate the specific effect of Vitamin E supplementation [22].…”
Section: Amyotrophic Lateral Sclerosismentioning
confidence: 96%
“…Both studies reported safe and well-tolerated drug administration, but no beneficial effect for ALS patients (Desnuelle et al, 2001;Graf et al, 2005). In a retrospective case-control study, high dosage of tocopherol decreased the risk of developing ALS (Veldink et al, 2007).…”
Section: Tocopherol (Vitamin E)mentioning
confidence: 97%
“…Thirdly, it is known that 10% of ALS cases are caused by genetic abnormalities (10); the proponents of Endotherapia do not appear to be carrying out any genetic testing to identify this subset. Fourthly, at least two components of the Endotherapia cocktail have been tested in human ALS and found to have no benefit (11,12); why these would be included in this cocktail is thus unclear. Finally, as of the date of this publication, there are no biomarkers, antibodies or otherwise, that have been demonstrated to confirm the trigger, identify downstream processes that drive progression, or plan successful treatment for patients with sporadic ALS.…”
Section: Mechanism(s)mentioning
confidence: 99%